Selecting a Superior Landing Area in the Region Far From Procellarum KREEP Terrane - Wenqing Chang; Zhiguo Meng; Xuegang Dong; Meng Zou; Xiaoping Zhang; Yuanzhi Zhang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The area far from the Procellarum KREEP Terrane (PKT) is important for future landing exploration. Mare Crisium, located in the area, has been identified as an essential landing option for the Lunar Geophysical Network (LGN) mission. Utilizing high-resolution images, topographic data, surface compositions, and Chang'e-2 microwave radiometer (MRM) data, a systematic analysis and comparison have been done between Maria Crisium and Smythii in terms of geomorphological feature, regolith properties, lunar crust and mantle properties, and microwave thermal emission characteristics. The results indicate that, except for investigating central magnetic anomaly in situ, Mare Smythii can complete all the scientific goals in Mare Crisium proposed by predecessors. Moreover, Mare Smythii has more complex geomorphology; the regolith here has a high detection priority including the cryptomare, swirls, and the probable water ice and volatile; and there exists the MRM anomaly, probably representing a new material that has not been detected until now. Generally, Mare Smythii should have a high priority for future exploration of the lunar surface in the region far from the PKT.